2008
DOI: 10.1177/1087054707308482
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ADHD With Amphetamine

Abstract: Objective: This research seeks to study the impact on family function after 3 months of treatment with amphetamine. Method: A total of 43 children, 6 to 11 years of age, with ADHD were treated with amphetamine for 3 months. Family function was studied before and after treatment by parent self-rating and independent observer ratings of videotaped parentchild interactions. Results: The families with a child with ADHD were found to be more dysfunctional than control families. Families with children with severe AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…For example, researchers have demonstrated that when adults interact with youth exhibiting ADHD behaviors, they engage in more negative parenting behaviors (Lang, Pelham, Atkeson, & Murphy, 1999; Wymbs et al, 2015). In addition, researchers have also reported that when children with ADHD were taking medication, their parents used more positive parenting strategies versus when the children were unmedicated, suggesting that reductions in child ADHD symptoms positively influenced parenting behaviors (Barkley, 1989; Gustafsson, Hansson, Eidevall, Thernlund, & Svedin, 2008). Together, both correlational and experimental research highlights that the association between aspects of parenting, like parental warmth, and child ADHD symptoms is bidirectional.…”
Section: Parental Warmth and Adhd Symptomsmentioning
confidence: 99%
“…For example, researchers have demonstrated that when adults interact with youth exhibiting ADHD behaviors, they engage in more negative parenting behaviors (Lang, Pelham, Atkeson, & Murphy, 1999; Wymbs et al, 2015). In addition, researchers have also reported that when children with ADHD were taking medication, their parents used more positive parenting strategies versus when the children were unmedicated, suggesting that reductions in child ADHD symptoms positively influenced parenting behaviors (Barkley, 1989; Gustafsson, Hansson, Eidevall, Thernlund, & Svedin, 2008). Together, both correlational and experimental research highlights that the association between aspects of parenting, like parental warmth, and child ADHD symptoms is bidirectional.…”
Section: Parental Warmth and Adhd Symptomsmentioning
confidence: 99%